ICGSCE 2014 Proceedings of the International Conference on Global Sustainability and Chemical Engineering - Hashim, Md Amin.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book includes selected papers from the ICGSCE 2014 with focus on the current trends of global resources used to meet the growing demands to improve life style coupled with environmental and social problems related to the resource consumption with emphasize to move towards sustainable development. It provides a platform for scientists and academicians from local and international universities and industries to promote, share and discuss various new issues and developments in different areas of Chemical Engineering with respect to global sustainability. Under the sustainability umbrella the topics covered are; alternative energy sources, alternative feedstock for energy and chemicals, alternative raw materials for household commodity, green process with minimal environmental impact, process intensification, waste minimization, recycling of wastes and providing quality water, food and medicines. Other topics covered include: 1. Oil and gas, Biofuel, Fuel cell, Renewable energy 2. Green technology, Sustainability, Environmental, Carbon sequestration, Carbon footprint, Natural resources 3. Chemical processes, Separation technology, Biotechnology, Nanotechnology, Food technology, Particle technology, Corrosion, Pharmaceutical, Phytochemical, Oleochemical 4. Process modeling, Process Simulation, Process control 5. Advanced material, Polymer, Catalyst, Enzyme 6. Policy, Regulations, Strategy and implementation, Safety, Management of science, Engineering education 7. Process Safety and Loss Prevention, Environmental and chemical risk assessment, Transportation risk analysis, Inherent safety.
Overview on Chemical-based, Bio-based and Natural-based Surfactants in EOR Applications -- OPEFB Filler from Biomass in Super Absorbent Polymer Composite for Agriculture Application: A Comparative Study -- Exploring Non-wood Plants as Alternative Pulps: From the Physical and Chemical Perspective -- Separation of Pyrrole from Iso-Decane Using Imidazolium and Pyridinium Based Ionic Liquid at 298.15K:Experiment and COSMO-RS Prediction -- The Development of Amine-Based Potential Kenaf Sorbent for Carbon Dioxide (CO2) Capture -- Potential Effect of Palm Oil Fuel Ash as Micro-Filler of Polymer Concrete -- Liquid Membrane Formulation for Succinic Acid Extraction from Simulated Aqueous Waste Solution -- Preservation of Natural Textile Colorant from Xylocarpus Moluccensis by Encapsulating into PVA Alginate -- Coagulant from Chemically Modified Fish Scale for Textile Wastewater Treatment -- Investigation of N-containing organic compound as corrosion inhibitor for carbon steel in saline environment -- Evaluation on the Effect of Inhibitor Ratio to the Wax Deposition in Malaysian Crude -- Solvent Extraction of Castor Beans Oil: Experimental Optimization via Response Surface Methodology -- Immobilization of nano-sized TiO2 on Glass Plate for the Removal of Methyl Orange and Methylene Blue.
Keywords: Chemical engineering; Sustainable development; Renewable energy resources; Materials science; Environmental engineering; Biotechnology; Energy policy; Energy and state; Industrial Chemistry/Chemical Engineering; Sustainable Development; Renewable and Green Energy; Materials Science, general; Environmental Engineering/Biotechnology.; Energy Policy, Economics and Management